CULTURAL LITERACY IN EDUCATION AND SOCIOCULTURAL ENVIRONMENT THE HISTORICAL PERIODS OF THE FOUNDING AND RENEWAL OF THE STATE OF LATVIA - Lodiņa, Solvita; Jurs, Pāvels (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The world’s geopolitical conflicts and ideological pluralism of society raise the importance of cultural literacy development in the micro and macro relations of different nations. After the Second World War, nations formed the United Nations Educational, Scientific and Cultural Organisations (UNESCO), to learn peaceful coexistence based on cultural values. Latvia as a UNESCO Member State since 1991, together with 25 European Union countries, developed a handbook on cultural awareness and expression in 2016, and in 2023 – a material for promoting cultural literacy among young people. Latvians’ love for their nation, language, and cultural heritage helped found their own country, Latvia, in 1918 and later, in 1991, to restore it, preserving its freedom to this day. In both historical periods and now, there have been minorities in Latvia. From 2023 onwards, education for them will be exclusively in Latvian. Therefore, in education and the socio-cultural environment, cultural literacy should be developed through the preservation of historical memory, patriotic education. The aim of the theoretical research is to find out the genesis of the concept of cultural literacy in relation to education in the socio-cultural environment of the founding-restoration period of the Latvian state. Using a quantitative method of systemic literature analysis; in the stage of qualitative analysis of historical documents, periodical content analysis, and data interpretation, it was concluded that the concept of cultural literacy in the educational content of the sociocultural environment of 1918-1940 can be seen in the United, Neighbourhood, Homeland, and Nationality teachings, but after 1991. - in the Latvian Folk Life Curriculum for Educators, in 1995, the program of the Latvian Latvian folklore education in the principle of educational methodology, 1995 in the Cultural Policy Guidelines - Chapter IV on General Education.